Deep Brain Stimulation (DBS) and Spinal Cord Stimulation (SCS) - Ethical considerations in the use of Implants and Bio-Medical responsibility at manufacture - Аref Хан (Archive of Biomedical Science and Engineering - Peertechz Publications, 2018)
Here in this brief we take a quick look into the use of certain biomedical devices and their benefits. At the same time, it is suggested that there are questionable practices by manufacturers, which raise concerns about corporate mores in general and around Ethics. As a Society, especially in these modern days, we need to be more aware of all that is going on and ensure accountability. Should not the primary objective be about saving lives and improving the quality of life, rather than putting the profit margin first. In this article we consider field of neuromodulation which is one of the fastest growing and the implantable devices such as pacemakers and IPGs. Let's start off with a bit of background.